(untitled) (Medical Forum Monthly, 2021)
Objective: To study the Level of Vitamin D3 Deficiency in Children Study Design: Observational study Place and Duration of Study: This study was conducted at the department of pediatrics, GMMC Medical College, Sukkur and Per Mirs Medical College, Khairpur Mirs during January 2019 to December 2020. Materials and Methods: We included the age six to twelve years patients, that attended the endocrinology department of pediatrics. We added sick children who attended clinic of our outpatient for detection of growth and age before puberty without any acute diseases on the day of visit. 230 samples were taken keeping in view exclusion criteria like seizers, low hormonal levels of thyroid gland. All those children whose weight lied in between 3 to 84 percentile were considered as normal, those with 85 to 94 percentile were considered as over weight .It was according to previous formulated standards in Korea. Among samples there were eighty girls (34.78%) and one hundred fifty boys (65.21%). Among the patients, one hundred fifty (62.21%) had a normal weight, fifty (21.73%) were overweight and obese thirty (13.04%). The written informed consent of the parents of the patients was taken before collecting the information. The Ethical Committee permission was taken before collecting the data and get publishing in Medical Journal. Results: The incidence of was maximum 120 (52.17%) at age 1-6 year and was 110(47.82%) at age group 7-10 year. Male children were 150 (62.21%) and female 80 (34.78%). There were 150 (62.21%) normal children, overweight 50 (21.73%) and obese 30 (13.04%) children. There was 45 (19.56%) cases in spring, 65 (28.26%) in Autumn and 120 (52.17%) cases in winter. There were 130 (56.52%) cases of vitamin D Deficiency and 100 (43.47%) of Sufficiency vitamin D. Conclusion: From current study it was resulted that feeble levels of serum Vitamin D were mainly encountered in children of school going age. It was also resulted that such feeble levels encountered in cold and blooming seasons. Therefore we suggest that it is necessary to supplement the vitamin D in diet according to our situation.